An application of hough transform to identify breast cancer in images - E.M.P. de F. Chagas (2008)
The present work focus on the identification of malignant neoplasias in breast by using the Hough Transform in digital images. A detector of circumference was implemented based on the Hough Transform once the pattern to identify is circular. The detector presented here was developed using MatLab, and was applied to detect circumferences in tomography images.